Lived Islam in South Asia - "Ahmad, Imitiaz.(ed.)" (New Delhi, 2011)
South Asia is probably the largest area in the world where Islam exists within a mixed composite culture, overlapping with several other religions. No matter how many origins of political conflicts one may find in the domain of culture and religion, there are, at the same time, elements of peaceful co-existence as well.
Keywords: Islam-South Asia